Telaah Pengkajian Qanun Aceh Nomor 6 Tahun 2014 Dalam Penanganan Kasus Kekerasan Seksual Di Indonesia (Tinjauan Aspek Konseptual Dan Politik Hukum) - Fitha Ayun Lutvia Nitha (UIN Syarif Hidayatullah Jakarta, 2025)
This article examines the effectiveness of Aceh Qanun Number 6 of 2014 on Jinayat Law in addressing sexual violence cases by focusing on its conceptual framework and legal-political orientation. Using a qualitative method with statute and conceptual approaches, this study analyzes the structure of criminal sanctions under the Qanun, its position within Indonesia’s plural legal system, and its implementation in the context of Aceh’s asymmetric decentralization. The study finds that although the Jinayat Qanun reflects a strong political will to institutionalize Islamic criminal law as a form of regional legal identity, its effectiveness in reducing sexual violence remains limited. This limitation is evident in the predominance of retributive punishment, such as caning and imprisonment, without adequate integration of victim protection mechanisms, restitution, and perpetrator rehabilitation. By situating the Qanun within broader debates on legal politics and criminal justice policy, this research demonstrates that punitive approaches alone are insufficient to address the complex social realities of sexual violence. The novelty of this article lies in its evaluative argument that the Jinayat Qanun represents a legal-political model of punishment that prioritizes symbolic deterrence over substantive justice for victims.